Obesity by High-Fat Diet Increases Pain Sensitivity by Reprogramming Branched-Chain Amino Acid Catabolism in Dorsal Root Ganglia - Lian, Nan; Luo, Kaiteng; Xie, Huijing; Kang, Yi; Tang, Kuo; Lu, Peilin; Li, Tao (Frontiers in Nutrition, 2022)
Obesity is a significant health concern as a result of poor-quality diet, for example, high-fat diet (HFD). Although multiple biological and molecular changes have been identified to contribute to HFD-induced pain susceptibility, the mechanisms are not fully understood. Here, we show that mice under 8 weeks of HFD were sensitive to mechanical and thermal stimuli, which was coupled with an accumulation of BCAAs in lumbar dorsal root ganglia (DRG) due to local BCAA catabolism deficiency. This HFD-induced hyperalgesic phenotype could be exacerbated by supply of excessive BCAAs or mitigated by promotion of BCAA catabolism via BT2 treatment. In addition, our results suggested that HFD-related pain hypersensitivity was associated with a pro-inflammatory status in DRG, which could be regulated by BCAA abundance. Therefore, our study demonstrates that defective BCAA catabolism in DRG facilitates HFD-induced pain hypersensitivity by triggering inflammation. These findings not only reveal metabolic underpinnings for the pathogenesis of HFD-related hyperalgesia but also offer potential targets for developing diet-based therapy of chronic pain.